Patients' and caregivers' needs in palliative care from the perspective of home care providers: A qualitative study. - Arantes, Vitória Mesquita; Jones, Jordan Cole; Giansante, Thais; Ribeiro, Simone Cristina; Pelegrino, Juliana; Bolela, Fabiana (Nursing Practice Today, 2025)
Background & Aim: Palliative care is an approach designed to enhance the quality of life and alleviate suffering associated with life-threatening illnesses. It should also be included in Home Care Services. This study aimed to identify the needs of patients in palliative care and their caregivers from the perspective of Home Care Service providers. Methods & Materials: This qualitative research study was conducted with a multidisciplinary team of providers under the Home Care Service program in the interior of São Paulo state, Brazil. Data were collected through semi-structured interviews and analyzed using the Content Analysis method. Results: Three categories emerged from the provider's narratives: insufficient knowledge about palliative care, the needs of patients in palliative care, and the needs of caregivers of patients in palliative care. Additionally, nine subcategories were identified: palliative care as end-of-life care, palliative care as an opportunity to provide comfort measures, lack of palliative care training for the multidisciplinary team, pain management, nutrition, emotional support, and psychological care, presence of family members, psychological support, and assistance in care management. Conclusion: This study identified the needs of patients in palliative care and their caregivers from the perspective of Home Care staff. The primary needs of patients, as identified by the staff, encompassed both physical and psychosocial support, including the presence of family members. For these patients' caregivers, staff emphasized the importance of psychological support and assistance in managing care. The study highlights the importance of continuous education in the home palliative care setting that recognizes the needs of both patients and caregivers.